2021
DOI: 10.3390/biomedicines9101378
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Activities of D-Chiro-Inositol: A Narrative Review

Abstract: D-chiro-inositol (DCI) is a natural compound detectable in cell membranes, which is highly conserved as a biological signaling molecule. In mammals, its function is primarily characterized in the intracellular transduction cascade of insulin. In particular, insulin signal promotes the release of pivotal DCI-containing molecules. In fact, impaired release of DCI is a common feature of insulin-resistant tissues, and insulin-sensitizing pharmaceuticals induce higher concentrations of free DCI. Moreover, it also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Considering our observations, we hypothesized that D-chiro-Ins and myo-Ins could perform their WAT/BAT trans-differentiation effects by an undefined mechanism involving the estrogen receptor; these results are also supported by a recent study by Montt-Guevara and collaborators [ 18 ], who demonstrated that D-Chiro-Ins can regulate human adipocytes (SGBS) directly, by enhancing their differentiation and insulin receptor signaling in synergy with estrogen. Nonetheless, two clinical trials in men showed that treatment with D-chiro-Ins significantly increased androgen levels and decreased estrogen levels [ 35 , 36 ], supporting its current therapeutic use in specific pathologies, i.e., those characterized by excessive estrogens or reduced androgens [ 37 , 38 , 39 ]. In this scenario, our current data opens a new window on the effects of these compounds and indicates that the mechanism of action of D-chiro-Ins and myo-Ins is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Considering our observations, we hypothesized that D-chiro-Ins and myo-Ins could perform their WAT/BAT trans-differentiation effects by an undefined mechanism involving the estrogen receptor; these results are also supported by a recent study by Montt-Guevara and collaborators [ 18 ], who demonstrated that D-Chiro-Ins can regulate human adipocytes (SGBS) directly, by enhancing their differentiation and insulin receptor signaling in synergy with estrogen. Nonetheless, two clinical trials in men showed that treatment with D-chiro-Ins significantly increased androgen levels and decreased estrogen levels [ 35 , 36 ], supporting its current therapeutic use in specific pathologies, i.e., those characterized by excessive estrogens or reduced androgens [ 37 , 38 , 39 ]. In this scenario, our current data opens a new window on the effects of these compounds and indicates that the mechanism of action of D-chiro-Ins and myo-Ins is more complex than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…GATA6 is an important androgen-production-related gene whose protein has been shown to stimulate the human CYP17 promoter activity [ 111 ]. IRS-2 is an insulin receptor gene whose products lead to increased PI3K activity and could further promote androgen production by regulating the activity of thecal 17α-hydroxylase [ 112 ]. Therefore, miR-92a and miR-92b downregulation may play a role in the androgen biosynthesis dysregulation in theca cells of women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…D-1,2,3,4,5,6-hexanehexol, is a Sorbitol, also called D-Glucitol in the systematic chemical nomenclature, is one type of sugar alcohol (polyols) used in food manufacturing and in medical tests. [39,40] D-Glucitol-derived sorbitan esters (spans)/ ethoxylated sorbitan esters (Tween) and other similar compounds have found widespread use in healthcare products, cosmetics, and the food industry. These substances serve as emulsifiers, stabilizers, and excipients.…”
Section: Quantitative Phytochemical Analysismentioning
confidence: 99%